Compliance among infants exposed to hepatitis B virus in a post-vaccination serological testing program in four provinces in China - Hui Zheng; Guo-Min Zhang; Po-Lin Chan; Fu-Zhen Wang; Lance Everett Rodewald; Ning Miao; Xiao-Jin Sun; Zun-Dong Yin; Jeffrey Edwards; Hua-Qing Wang (BMC, 2019)
Abstract Background Mother to child transmission of hepatitis B virus (HBV) remains the most common form of HBV infection in China. Prevention of HBV vertical transmission involves timely administration of the complete hepatitis B vaccine (HepB) series and hepatitis B immunoglobulin. Post-vaccination serological testing (PVST) is utilized to determine an infant's outcome after HBV exposure and completion of HepB series. We aim to determine the frequency of compliance with a PVST testing cascade for HBV infected mothers and analyze factors associated with infant lost to follow up (LTFU). Methods We conducted a retrospective cohort review of previously collected data in Fujian, Jiangxi, Zhejiang and Chongqing provinces in China from 1 June 2016-31 December 2017. The study population included all HBV-exposed infants and their mothers. SAS software was used for statistical analyses. Bivariate and multivariate regression analyses (presented in odds ratio [OR] with 95% confidence intervals [CI]) were used to compare the proportional differences of factors associated with PVST not being completed. Results Among enrolled 8474 target infants, 40% of them transferred out of the study provinces without further information and 4988 were eligible for PVST. We found 20% (994) of infants were not compliant with the testing cascade: 55% of LTFU occurred because parents refused venous blood sample collection or failure of sample collection in the field, 16% transferred out after 6 months of age, and 10% of families chose to have independent, confidential PVST completed without reporting results. High PVST noncompliance rates were more likely to be from Fujian (aOR = 17.0, 95% CI: 9.7-29.9), Zhejiang (aOR = 5.7, 95% CI: 3.2-10.1) and Jiangxi (aOR = 1.9, 95% CI: 1.0-3.4), and from HBV e antigen positive mother (aOR = 1.2, 95% CI: 1.1-1.4). Conclusions This study found that the LTFU rate reached 20% in PVST program, which was a significant problem. We recommend implementing a national electronic information system for tracking HBV at risk mother-infant pairs; encourage further research in developing a less invasive means of completing PVST, and take effective measures nationally to reduce HBV stigma. Without reducing the loss to follow up rate among infants eligible for PVST, elimination of vertical HBV transmission will be impossible.